The Effect of Sodium Thiosulfate on Coronary Artery Calcification in Hemodialysis Patients. Issue 3 (March 2022) - Bian, Zhixiang; Zhang, Qin; Shen, Li; Feng, Yanping; Chen, Shunjie
Abstract : This study aimed to effectively control the disease process of hemodialysis outpatients. Hemodialysis secondary hyperparathyroidism patients were randomly divided into the control group and treatment group. The control group was treated with routine treatment, and the treatment group was treated with sodium thiosulfate based on the control group. The changes of serum calcium, phosphorus, whole parathyroid hormone, calcium-phosphorus product and coronary artery calcification (CAC) score, as well as the relief of clinical symptoms, postoperative complications and recurrence in the preoperative and postoperative periods were observed. The levels of C-reactive protein and CAC scores were significantly decreased in the treatment group after treatment. While there was no significant difference in blood calcium, blood phosphorus, PTH, calcium-phosphorus product, and CAC score in the control group after treatment. And after treatment, the proportion of skin pruritus, myasthenia, bone pain, insomnia, restless legs syndrome, and other symptoms in the treatment group was significantly decreased compared with those before treatment, but there was no significant change in the control group before and after treatment. Sodium thiosulfate can reduce the high level of CAC in hemodialysis patients obviously.